Paediatric lateral humeral condyle fractures managed by k-wire fixation, should the wires be buried or left exposed: a dilemma - Choudhary, Nitin; Gupta, Sanjeev; Mahajan, Neeraj; Mahajan, Rahul; Saharan, Amar (International Journal of Research in Orthopaedics, 2020)
Background: Fractures of the lateral condyle of the humerus in children are common injuries. If displaced or unstable they may require surgical reduction and fixation with Kirschner wires (K-wires). These may be passed through the skin and left exposed or buried subcutaneously. Methods: A prospective study was carried out in department of orthopaedics at my college from January 2019 to March 2020. A total number of 37 subjects were included in the study. Results: Patients were followed for a period of 3 months and results were drawn on basis of union, infection, carrying angle at the elbow, and range of motion (ROM) which was assessed by clinico-radiological means. Conclusions: Buried wire group has shown better union rate than exposed group, wires could be removed under local anaesthesia thereby avoiding any major procedure and also the risk of infection is low making this a better option than the exposed cohort.